2020
DOI: 10.1186/s12864-020-6626-9
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry-specific associations identified in genome-wide combined-phenotype study of red blood cell traits emphasize benefits of diversity in genomics

Abstract: Background: Quantitative red blood cell (RBC) traits are highly polygenic clinically relevant traits, with approximately 500 reported GWAS loci. The majority of RBC trait GWAS have been performed in European-or East Asian-ancestry populations, despite evidence that rare or ancestry-specific variation contributes substantially to RBC trait heritability. Recently developed combined-phenotype methods which leverage genetic trait correlation to improve statistical power have not yet been applied to these traits. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
(87 reference statements)
1
17
0
Order By: Relevance
“…This expectation nicely conforms with empirical data, mostly from QTL studies, which find heterogeneous sets of contributing loci among different populations (Adeyemo et al 2009;Wu et al 2013;Al Olama et al 2014;Li and Keating 2014;Conte et al 2015;Horikoshi et al 2018;Takata et al 2019;Wojcik et al 2019;Zan and Carlborg 2019;Hodonsky et al 2020). In the case of adaptation to a new trait optimum, genetically differentiated populations will adapt by frequency changes of different sets of loci.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This expectation nicely conforms with empirical data, mostly from QTL studies, which find heterogeneous sets of contributing loci among different populations (Adeyemo et al 2009;Wu et al 2013;Al Olama et al 2014;Li and Keating 2014;Conte et al 2015;Horikoshi et al 2018;Takata et al 2019;Wojcik et al 2019;Zan and Carlborg 2019;Hodonsky et al 2020). In the case of adaptation to a new trait optimum, genetically differentiated populations will adapt by frequency changes of different sets of loci.…”
Section: Introductionsupporting
confidence: 87%
“…Various studies, mainly using QTL mapping and GWAS, have identified different loci contributing to the same trait in diverged populations (Adeyemo et al 2009;Wu et al 2013;Al Olama et al 2014;Li and Keating 2014;Conte et al 2015;Horikoshi et al 2018;Takata et al 2019;Wojcik et al 2019;Zan and Carlborg 2019;Hodonsky et al 2020;Kemppainen et al 2020). A recent experimental evolution study using D. subobscura populations with different genetic background also observed very little overlap in the genomic regions responding to a common selection regime (Seabra et al 2018).…”
Section: Population-specific Adaptive Architecturesmentioning
confidence: 99%
“…Here, we conducted large-scale TWAS meta-analyses for 4 blood cell traits in AA and HL populations, using a larger whole-blood eQTL reference panel (DGN) in European ancestry populations and smaller but ancestry-matched reference panels from MESA monocytes. To our knowledge, this is the largest genetic discovery effort yet conducted in these populations for blood cell indices, exceeding available sample sizes from recent trans-ethnic blood cell traits GWAS ([ 38 ], n = 15,171 African ancestry, n = 9368 Hispanic/Latino), recent analyses of red blood cells in the Population Architecture using Genomics and Epidemiology [PAGE] studies ([ 54 ], n = 16,258 African American, n = 20,784 Hispanic/Latino), and our own recent TOPMed imputed GWAS analyses ([ 55 ], n = 21,513 African ancestry and 21,689 Hispanic/Latino participants). These previous efforts all included some but not all of the cohorts included here.…”
Section: Discussionmentioning
confidence: 99%
“…Haplotype blocks are identified and characterized by SNPs with a correlated allele frequency change after multiple generations of experimental evolution [6]. [27][28][29][30][31][32][33][34][35][36]. In the case of adaptation to a new trait optimum, genetically differentiated populations will adapt by frequency changes of different sets of loci.…”
Section: Genomic Regionmentioning
confidence: 99%